Identification of a seasonal pattern to brain metastases - Sakellakis M; Koutras A; Pittaka M; Kardamakis D; Kalofonou M; Kalofonos H; Spyropoulou D (Neuropsychiatric Disease and Treatment, 2016)
Minas Sakellakis,1 Angelos Koutras,1 Maria Pittaka,2 Dimitrios Kardamakis,2 Melpomeni Kalofonou,1 Haralabos P Kalofonos,1 Despina Spyropoulou2 1Division of Oncology, Department of Medicine, 2Department of Radiation Oncology, University Hospital, Patras Medical School, Rion, Patras, GreeceWe have previously tested our hypothesis that there is a seasonality in the incidence of carcinomatous meningitis.1 Although further validation is needed in a larger cohort, we found that leptomeningeal metastasis occurred more often during warm months of the year which, in the case of Greece, is the period generally marked with the larger daytime length.1 Carcinomatous meningitis is closely related to brain metastasis, and a logical question is whether warm season is marked by a greater propensity also for brain metastasis.2